Eastern Pacific scorpionfish Scorpaena mystes and Scorpaena plumieri (Perciformes: Scorpaenidae) from the coast of Brazil: two geminate species with very similar venoms - Diaz Oreiro, Cecilia (2026)
Some studies have shown phylogenetic proximity between the scorpionfish species Scorpaena plumieri and Scorpaena mystes, despite having inhabited different oceans for millions of years. The former occurs in the Western Atlantic Ocean, including the Caribbean Sea, and the latter inhabits the Eastern Pacific. The venom of S. plumieri from tropical Atlantic reefs has been widely studied, whereas that from S. mystes has not been characterized. To determine whether the venom of S. mystes reflects the previously shown phylogenetic proximity between these species, we performed a proteomics study and analysed its biochemical activities. We identified proteins with similarity to the characteristic cytolysin α- and β-subunits of S. plumieri, as well as putative pore-forming toxins from the venom of other scorpionfish species. As in many scorpaenoid taxa, several of the identified components are coming from the epidermal mucus, produced by mucus glands, leukocytes or other potential organisms living on their skin. This is the case of the mucus B- and C-type lectins identified in S. mystes, which are homologues to those from S. plumieri. The analysed venom also displays hyaluronidase and proteolytic activities, and can induce hemolysis, hemagglutination and nerve membrane permeabilization. In conclusion, regarding their venoms, S. mystes and S. plumieri appear to be closely related lineages inhabiting different marine ecosystems.